Rock progressif et violence politique : illustrations en Italie et en France avec les groupes Stormy Six et Komintern - Jean-René Larue (Criminocorpus)
Contrary to popular belief, the history of progressive rock is not exempt from some kind of violence, particularly symbolic and political. The goal of this article will be to demonstrate the different forms that political violence has taken in progressive rock by study of the Italian group Stormy Six and the French group Komintern. For that we will show the place of the communist in the Italian peninsula as well as that of the situationist thought in France. The comparison of the two groups will allow us to highlight the place of political and symbolic violence in the progressive rock of the 1960s and 1970s but also to illustrate the influence of national contexts on this music.